2015
DOI: 10.1039/c5dt01134e
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene/fullerene hybrids showing large second-order nonlinear optical activities: impact of the cage unit size

Abstract: The electron donor-acceptor complexes, which undergo intramolecular charge transfer under external stimulus, are an emerging class of materials showing important application in nonlinear optics. Synthesizing ferrocene/fullerene complexes through face-to-face fusion would enjoy the merits of both ferrocene and fullerene due to their strong donor-acceptor interactions. Four ferrocene/fullerene hybrid complexes with the gradual extension of fullerene cage size, including CpFe(C60H5), CpFe(C66H5), CpFe(C70H5), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…The dipole moment is generally associated with the projection of β on dipole moment vector (β vec ). [55][56] The definition of β vec is b vec ¼ P i¼x;y;z…”
Section: Nlo Properties Of Gy[1]à (Ch=ch)mentioning
confidence: 99%
“…The dipole moment is generally associated with the projection of β on dipole moment vector (β vec ). [55][56] The definition of β vec is b vec ¼ P i¼x;y;z…”
Section: Nlo Properties Of Gy[1]à (Ch=ch)mentioning
confidence: 99%
“…Hasheminia et al, 32 Yin et al, 13 Jiang et al, 22 Wang et al, 36 Xi et al, 35 Méar et al, 37 and Ji et al 34 produced different foamed glasses, ceramics and building insulation materials using SiC as a foaming agent. Besides, Bernardo et al 38 reported using glass foams from recycled soda-lime glass and SiC-based waste as the foaming agent.…”
Section: Effect Of the Foaming Agent Content On The Cfsmentioning
confidence: 99%
“…The B3LYP functional, a combination of Becke's three-parameter hybrid exchange functional and the Lee-Yang-Parr correlation functional, has been widely used in geometrical optimizations. [33][34][35] Harmonic vibrational frequency calculations were used to conrm that the optimized structures were minima, as characterized by positive vibrational frequencies.…”
Section: Computational Detailsmentioning
confidence: 99%